Online Learning - Marietta Stanton (Online Journal of Rural Nursing and Health Care, 2012)
Learning online is all the rage today and with good reason. It provides a level of access and convenience that is not possible with traditional forms of education. This is especially true for rural nurses who may be miles away from academic centers and wish to pursue a degree. It also may be a convenient source of continuing education and staff development for working nurses who need an update on information in their area of practice.